Randomized Controlled Pilot Study of Video Self-assessment for Resident Mastoidectomy Training. Issue 2 (April 2018) - Jethwa, Ashok R.; Perdoni, Christopher J.; Kelly, Elizabeth A.; Yueh, Bevan; Levine, Samuel C.; Adams, Meredith E.
A prospective randomized controlled pilot study was performed to determine if video self-assessment improves competency in mastoidectomy and to assess interrater agreement between expert and resident evaluations of recorded mastoidectomy. Sixteen otolaryngology residents were recorded while performing cadaveric mastoidectomy and randomized into video self-assessment and control groups. All residents performed a second recorded mastoidectomy. Performance was evaluated by blinded experts with a validated assessment scale. Video self-assessment did not lead to greater skill improvement between the first and second mastoidectomy. Interrater agreement was fair to substantial between the expert evaluators and between resident self-evaluations by recall and video review. Agreement between experts and residents was only slight to fair; residents consistently rated their performance higher than experts ( P < .05). In conclusion, 1 session of video self-review did not lead to improved competence in mastoidectomy over standard practice. While experts agree on assessments, residents may overestimate their competency in performing cadaveric mastoidectomy.